Derivatif Radial Anomali Gravitasi Untuk Identifikasi Batas Vertikal Pada Lapisan Tunggal - Muhammad Zuhdi; Syahrial Ayub; Muhammad Taufik (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2020)
The purpose of this study is to make and test radial derivatives for identification of single layers. Radial Derivatives are derivatives of gravitational anomaly values with respect to the horizontal distance in the radial direction of a particular point. The center of the derivative is chosen based on consideration as the center of the anomaly of target. Several synthetic single layer models have been made in the form of temple artifacts and water table changes over time. From these models, the gravity anomalies are calculated forward. Radial derivatives of these anomalies are performed to determine the vertical boundary of a single layer. Radial derivatives in a single layer of temple artifacts are useful for determining the boundaries of temple walls, so that the analysis of artifact excavation points can be better determined. Radial derivatives in anomalies in water table changes over time are useful for sorting shallow gravity anomalies which have significant value. The result of this research shows that radial derivative is able to detect boundary of buried temple and also boundary of water table. The advantage of the radial derivative method is that it is not necessary to re-measure if gravity data has been previously measured. In other words, this method is a software to review the further analysis that might have been done before.